The Expansion of Legal Application of Military Law on Legal Subjects that Equated with the Military Based on Republic of Indonesia Law - Ilman Hadi; Irwan Triadi; Parluhutan Sagala (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2025)
A nation as an entity needs a way to maintain its existence as best as possible through its own capabilities through a national military formed to carry out national defense duties. Generally, the term "military" refers only to active and organic military personnel. Subsequently, a group of individuals legally equated with the military emerged. During President Soekarno's administration, Indonesia implemented compulsory military service to encourage greater public involvement in the armed forces. Currently, there are also other groups considered military, including student soldiers, titular military personnel, and citizens mobilized as reserve component troops. The increase and expansion of the number of individuals considered military has an impact on the application of military law, as they are included within the military legal system. The theory of legality is used to analyze this issue qualitatively. The Ministry of Defense is obligated to foster and develop military law in Indonesia, including all military legal entities. Without clear regulations on the application of military law, issues of military judicial jurisdiction over individuals legally equated with the military will arise.